Peranan Digital Economy dalam Menilai Keakuratan Data Output Keuangan: Studi Kasus Cafe Harman - Nadya Andreyanto; Anindya Frysa Irsyadi; Selma Nevira Shinta Putri; Maria Yovita R. Pandin (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research was carried out at Cafe Harman to determine the role of the digital economy in assessing the accuracy of financial output data at Cafe Harman. The methodology used is qualitative, using primary data sources, to collect data through interviews and documentation. The research results found show that Kasir Pintar has the features needed by Cafe Harman to develop its business because the features of Kasir Pintar have more accurate data output.